PENGARUH MODEL PEMBELAJARAN BISNIS BERISIKO TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMP TRI BHAKTI PEKANBARU - Fitdiya Rizki; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by the low PPKn learning motivation of students at SMP Tri Bhakti Pekanbaru. The formulation of the problem in this study is: "Is there any influence on the use of Business Risk learning models on PPKn Learning Motivation for VIII grade students at SMP Tri Bhakti Pekanbaru?”. This study aims to determine the effect of the use of a risky Business learning model on PPKn Learning Motivation for VIII grade students at SMP Tri Bhakti. This research was conducted at Tri Bhakti Pekanbaru Middle School in July 2018. And is a quantitative descriptive research that is experimental. The population in this study were eighth grade students at SMP Tri Bhakti Pekanbaru. The sample in this study was taken based on the technique "Random Sampling”. Where the classes taken as samples are students of Class VIII (1) students (experimental class) who were given a Risk Business learning model and VIII (2) class students (control class) were students who were given conventional methods. Then analysis data using homogeneity and t-test and gain test.Based on the results of the study showed that there was an effect of PPKn learning motivation between students who used risky business learning models with conventional methods at SMP Tri Bhakti Pekanbaru (>). Thus there is anThe Effect Of Risk Business Learning Models On PPKn Learning Motivation Of Class VIII Students At Smp Tri Bhakti Pekanbaru. This means that there is an influence between the risky business learning model and the learning motivation of the magnitude of the influence after it is calculated with a gain test showing the risky learning model of business gives an effect on learning motivation of 0.72. And there was an average increase in PPKn learning motivation in the experimental class from 41.12 to 43.06 and the increase in the average control class learning motivation of the control class from 29.85 to 30.05. Keywords: Risk Business, Learning Motivation